SISTEM PAKAR DIAGNOSA PENYAKIT UTAMA PADA TANAMAN KUBIS DENGAN MENGGUNAKAN METODE ADAPTIVE FUZZY INTERFERENCE SYSTEM - Sianipar, Fitri Nur Indah Sari; Hasibuan, Nelly Astuti; Nasution, Surya Darma (STMIK Budi Darma, 2019)
Cabbage (Brassica oleracea var Capitata) or commonly called cabbage is a cultivated vegetable, cabbage vegetables grow on high mountainous land and fertile so that the productivity of cabbage vegetables is very high. In cultivated plants, plant disease is one of the factors that can cause failure of crop production. Diseases of annual plants, including cabbage. Cabbage can attack all stages of cabbage development, from seed production to the stage of producing plants. ANFIS is a combination of system fuzzy interface mechanisms described in neural network architecture.